Гадаад хэл сургалтын арга зүйн хөгжлийн чиг хандлага: Methodlogical devеlopment trends in foreign language teaching - Sh., Tuya (Mongolian Journal of Foreign Languages and Cultures, 2023)
In the article, the author made an analysis on the latest articles about teaching theory and practice. Based on the analysis, she defined the dominant approaches of foreign language teaching methodology development. According to the author, there are following approaches: Communicative approaches to foreign language teaching. For example, teaching inter-cultural communication Develop lingua-cultural personal from all perspectives Introduce the innovation technology on foreign language teaching Use latest information and communication technology Update assessment system of learners’ knowledge, ability and skill Qualify foreign language teachers and improve the teacher training system Innovate the system to prepare specialists with foreign languages Develop and implement national standard to teach the first and second language in the framework of national education standard